2017
DOI: 10.1007/s40843-017-9121-y
|View full text |Cite
|
Sign up to set email alerts
|

Side-chain effect of organic semiconductors in OFET-based chemical sensors

Abstract: Organic field-effect transistors (OFETs) offer great potential applications in chemical and biological sensing for homeland security, environmental monitoring, industry manufacturing, and medical/biological detection. Many studies concentrate on sensitivity and selectivity improvement of OFET-based sensors. We report four organic semiconductors with different alkyl side chain lengths but the same π-conjugated core structure for OFETs. Our work focuses on the molecular structure of organic semiconductors (OSCs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…[36,37] The idea was based on the possibility of chain stacking (crystalline) changes according to the side (alkyl) groups attached to the main polymer backbones. [38][39][40] For this purpose, 2,5-bis-(2-octyldodecyl)-3,6-bis-(5-trimethylstannanylthiophen-2-yl)-2,5-dihydro-pyrrolo [3,4-c]pyrrole-1,4-dione (2Sn-ODTPPD) was reacted with 4,7-dibromo-2,1,3-benzothiadiazole (2Br-BT) in the presence of a Stille coupling catalyst. The resulting conjugated polymer, poly[{2,5-bis-(2-octyldodecyl)-3,6-bis-(thien-2yl)-pyrrolo [3,4-c]pyrrole-1,4-diyl}-co-{2,2′-(2,1,3-benzothiadiazole)-5,5′-diyl}] (PODTPPD-BT), exhibited strong optical absorptions in the NIR range.…”
Section: Introductionmentioning
confidence: 99%
“…[36,37] The idea was based on the possibility of chain stacking (crystalline) changes according to the side (alkyl) groups attached to the main polymer backbones. [38][39][40] For this purpose, 2,5-bis-(2-octyldodecyl)-3,6-bis-(5-trimethylstannanylthiophen-2-yl)-2,5-dihydro-pyrrolo [3,4-c]pyrrole-1,4-dione (2Sn-ODTPPD) was reacted with 4,7-dibromo-2,1,3-benzothiadiazole (2Br-BT) in the presence of a Stille coupling catalyst. The resulting conjugated polymer, poly[{2,5-bis-(2-octyldodecyl)-3,6-bis-(thien-2yl)-pyrrolo [3,4-c]pyrrole-1,4-diyl}-co-{2,2′-(2,1,3-benzothiadiazole)-5,5′-diyl}] (PODTPPD-BT), exhibited strong optical absorptions in the NIR range.…”
Section: Introductionmentioning
confidence: 99%
“…Air stability is one of the most important issues for meeting the requirements in practical applications [17][18][19][20][21]. In previous studies, organic materials affected by air environment have been widely studied [22,23]. It has been reported that for gate dielectric materials with active functional groups, such as hydroxyl groups, the interaction with the adsorbed water in air would affect the device performance [24,25], leading to performance degradation in air [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…There are about half a billion automobiles on the roads every day. This makes people's lives more convenient but also generates large amounts of pollutant gases, such as carbon monoxide (CO), nitric oxide (NO), ammonia (NH 3 ), and volatile organic com-pounds (VOCs) [4][5][6][7][8][9][10][11][12]. None of NH 3 , CO, or NO can be detected by the human senses.…”
Section: Introductionmentioning
confidence: 99%